Formulation and characterization of bar, paste, and liquid soaps using recycled cooking oil - Fadzil, Adibatul Husna; Zulkifli, Norsakina Zurina; Salleh, Nunshaimah; Ali, Rosliza; Mohd Noor, Adibah; Mohamed, Siti Mazleena; Pasma, Satriani Aga (2025)
This research focuses on the development of soaps formulated from the recycled cooking oil as the primary raw material. The objective was to produce soaps capable of effectively reducing bacterial presence, suitable for all skin types, and available in three distinct forms: solid, paste, and liquid. The formulations were prepared by combining sodium hydroxide, distilled water, and repurposed cooking oil, with lime juice incorporated for its antibacterial properties. The physicochemical evaluations were conducted to examine parameters such as pH stability, foaming capacity, allergenic potential, and colour. The results show the potential of upcycling waste materials into consumer-friendly soap products.